‘GOLDEN MOMENT’ FOR USM IN WINNING THE IEEE DARREL CHONG STUDENT ACTIVITY AWARD 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 15 September 2016 Universiti Sains Malaysia (USM) created history after emerging as the only higher learning institution in Malaysia to receive the Gold Award among 13 other international educational institutions at the IEEE Darrel Chong Student Activity Award 2016.